Web Based Parking Management and Reservation System - Ibrahim, Hamdi Khalifa Emhemmed (2010)
Information Technology plays a vital role in people's life today. Every aspect of human life is being computerized in order to improve the efficiency of these processes. As countries develop people tend to move towards cities expecting better quality of life. This makes cities over crowed in turn creating new problems. People need to move around to get their day to day work done. Today people prefer travel by vehicles even for short distances as vehicles become cheaper and vehicles provide a comfortable commute. Because of this today's cities have become over crowded with vehicles and traffic jams are characterized as the order of the day. Finding a suitable parking space in a crowded city is very difficult today. This problem becomes more acute in places that are commonly patronized by many people like shopping malls, restaurants, theatres etc., Sometimes people drive in circles looking for a suitable parking lot. This creates more problems such as more traffic, waste of time and money and environmental degradation. In this study, the parking problem has been looked at depth and a solution using the most advanced information technologies has been developed. The Web based Parking Management and Reservation System developed in this project is an advanced system that helps users to check the availability of parking spaces and book in advance. Prior to developing the system, a thorough literature survey has been canied out in order to understand the problem properly. Then the application has been designed and developed properly by following the suitable software engineering theories and practices. System design has been done using use case diagrams, sequence diagrams and class diagrams. The diagrams are developed using Unified Modeling Language the post popular modeling language. The system has been developed using advanced technologies including JAVA as the programming language on .NET framework using JSP 2.0 as the Integrated Development Environment (IDE). The back end database was developed using MS SQL Server. Finally the system has been tested for usability and ease of use through a sample survey. The result of the survey which is given in Chapter 5 proves that the system is extremely user friendly and the interfaces provide all the necessary tools for a smooth and friendly experience.